Supplementing semen extenders with a combination of phosphorus and vitamin B12 Improves post-thawed cryopreserved rooster semen quality - Suwimonteerabutr, Junpen; Ketkaew, Punnapon; Netiprasert, Gitsanai; Khaopong, Chidchanok; Osiriphan, Boonyaporn; Sriamornrat, Pawarisa; Nuntapaitoon, Morakot (Frontiers in Veterinary Science, 2023)
Semen cryopreservation is an important technique for preserving the genetic material of numerous species. However, frozen semen is highly susceptible to sperm DNA damage and reduced motility, resulting in decreased fertility. The standard method for cryopreservation and several approaches have not been elucidated. This study aimed to determine the effects of supplementing rooster semen extender with a combination of phosphorus and vitamin B12 on cryopreserved semen quality. Semen was collected weekly via dorso-abdominal massage from 57 Burmese × Vietnam-crossbred Thai native roosters aged 1-3 years. In total, 139 semen samples were collected, pooled, and diluted to 200 million sperm per dose. The pooled sample was divided into six experimental groups: a control group (0.00%) diluted with modified Beltville Poultry Semen Extender (BPSE) and five treatment groups diluted with modified BPSE supplemented with phosphorus and vitamin B12 at concentrations 0.02%, 0.04%, 0.06%, 0.08%, and 0.10%, respectively. The semen samples were frozen and evaluated at 0, 15, and 30 min after thawing. Sperm kinematic parameters were determined using a computer-assisted sperm analysis system. Sperm quality was evaluated by measuring sperm viability, mitochondrial activity, acrosome integrity, and plasma membrane integrity. Statistical analyses were performed using a general linear mixed model (MIXED) in SAS. Factors in the statistical model were experimental groups, time after thawing, and interaction between experimental groups and time after thawing. Total and progressive motilities were greater in semen supplemented with 0.04% phosphorus and vitamin B12 compared with those in the control (P < 0.05). At 15 min post-thawing, VCL, VAP, and HPA in the 0.04% phosphorus and vitamin B12 supplementation group was greater than that in the control (P < 0.05). Phosphorus and vitamin B12 supplementation did not affect sperm kinematics at 0 and 30 min after thawing (P > 0.05). All the sperm parameters that were tested for the 0.04% phosphorus and vitamin B12 supplementation group in modified BPSE were the highest at all the timepoints after thawing. Thus, supplementing frozen semen extender with 0.04% phosphorus and vitamin B12 increased sperm motility, sperm kinematic parameters, and sperm quality.